Formation of a macro-region for the effective management of the industrial complex (Nexo Revista Científica, 2022)
When justifying the relevance of the research task of measuring the contribution of macroregions to the country's economy, which has not yet found a scientific and methodological solution, it should be emphasized that the scientific literature does not present a system of parameters for assessing the contribution of macroregions to the national economy, there are practically no comprehensive methods for analyzing the impact of the functioning of macroregional socio-economic systems on the development of the country's economy. The article is devoted to the scientific and theoretical research of methodological approaches to determining the importance of macroregional socio-economic systems. A system of indicators is proposed for assessing the role of a macroregion in the national economy, reflecting its specificity as an integration territory and characterizing the level, degree and intensity of interaction between the actors of the macroregional economic and industrial complex.